Mirror, mirror - Robb, J. D., 1950-; Blayney, Mary; Fox, Elaine; McComas, Mary Kay; Ryan, R. C., 1937- (Jove Books, 2013)
Presents five romantic suspense novellas based on fairy tales, including J.D. Robb's "Taken in Death," a twist on the Hansel and Gretel story in which Eve Dallas searches for a pair of missing twins.